Trudności wychowawcze w edukacji przedszkolnej. Zarys problematyki = Behavioural difficulties in pre-school education. Outline of the problem - Puhacz, Daria (Zielona Góra: Uniwersytet Zielonogórski, Wydział Pedagogiki, Psychologii i Socjologii)
Article is about problem of pre-school behavioural difficulties. It shows theoretical basic on behavioural difficulties, their causes, effects and ways of prevention and competence of teachers necessary for working with chilren manifesting behavioural disorders. Presenting research results regarding teachers opinion about behavioural dificullties, ways to deal with them and methods used for educational work.
Keywords: trudności wychowawcze; edukacja przedszkolna; metoda aktywna; kompetencje nauczyciela; behavioural difficulties; pre-school education; active method; competence of teacher